2019
DOI: 10.18273/revion.v32n2-2019003
|View full text |Cite
|
Sign up to set email alerts
|

Co-digestión anaerobia de estiércoles bovino, porcino y equino como alternativa para mejorar el potencial energético en digestores domésticos

Abstract: Los digestores domésticos han sido utilizados para la gestión y valorización energética de estiércoles, en procesos de mono-digestión anaerobia. Sin embargo, el conocimiento es limitado con respecto a los rendimientos de biogás a partir de la co digestión de estiércoles. En este sentido, el objetivo de esta investigación fue determinar, mediante un diseño experimental usando la sinergia (Φ) como un indicador, las relaciones de mezcla adecuadas para digestión anaerobia de estiércoles, contribuyendo a o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
2
0
2
Order By: Relevance
“…The operational parameters of the digester are summarized in Table 2. Previous studies carried out with porcine manure reported that a 1:7 dilution favors the hydrolytic and methanogenic activities and the biomethane potential of the process [33]. Regarding the organic matter, the average VS of the influent decreased from 12.74 ± 3.52 g VS/kg to a mean value of 2.86 g ± 1.20 g VS/kg, which means an organic matter removal around 77.58%.…”
Section: Thermal Behavior Of the Digestermentioning
confidence: 80%
“…The operational parameters of the digester are summarized in Table 2. Previous studies carried out with porcine manure reported that a 1:7 dilution favors the hydrolytic and methanogenic activities and the biomethane potential of the process [33]. Regarding the organic matter, the average VS of the influent decreased from 12.74 ± 3.52 g VS/kg to a mean value of 2.86 g ± 1.20 g VS/kg, which means an organic matter removal around 77.58%.…”
Section: Thermal Behavior Of the Digestermentioning
confidence: 80%
“…Therefore, future research can analyze the effect of this type of inoculum on AD using additives such as BC. Castro-Molano et al [ 106 ] mention that it is usual for farms to have manure (bovine, pig, or equine). Therefore, these three wastes can be jointly valued with those generated in other productive processes (agricultural), helping to increase methane production.…”
Section: Resultsmentioning
confidence: 99%
“…Para valorar este tipo de variables, es conveniente que en el proceso haya flujo continuo, lo cual se logra diluyendo el estiércol con agua. En el caso de la presente investigación, se determinó como adecuada una proporción de 1:7 (promedio), la cual coincidió con la que (Castro et al, 2019), han utilizado como mejor opción en estudios con estiércol porcino.…”
Section: Subproductos Biogásunclassified